أثـــر برنامج تدريبي لتنمية القدرة الحسابية لدى تلاميذ ذوي صعوبة الرياضيات - بوعمرة، حنان, واسع، نوال (جامعة الوادي university of Eloued, 2021)
الملخص: هدفت الدراسة الى بناء برنامج تدريبي لتنمية القدرة الحسابية لدى تلاميذ السنة الرابعة والخامسة ابتدائي اللذين يعانون من صعوبة في الرياضيات، والتعرف على الفرق في القياس البعدي بين المجموعة الضابطة والتجريبية. وتم اجراء الدراسة على عينة تكونت من (20) تلميذ وتلميذة في بعض ابتدائيات الوادي، وقد تم اختيارهم بطريقة قصدية، و باستخدام اختبار يقيس القدرات القرائية بمختلف مستوياتها وقد تمثلت في الآتي: اختبار القدرة على الحساب الذهني ( جمع وطرح وضرب وقسمة الاعداد شفهيا)، واختبار القدرة على العد التنازلي، وبإتباع المنهج التجريبي ذو التصميم التجريبي بمجموعتين ضابطة وتجريبية، وقياسين قبلي وبعدي، ولاختبار فرضيات الدراسة تم استخدام المتوسط الحسابي والانحراف المعياري، وتم تطبيق اختبار "ت" لدلالة الفروق بين المتوسطات لعينتين مرتبطتين، ثم حساب حجم الاثر، وتم التوصل الى النتائج التالية: ان البرنامج التدريبي قد حقق اثرا ايجابيا في تنمية القدرة الحسابية لدى التلاميذ عسيري الحساب وذلك على مستوى القدرة على الحساب الذهني، حيث تم توصل الى انه توجد فروق ذات دلالة احصائية في القياس البعدي بين المجموعة الضابطة والتجريبية. وقد حقق اثر ايجابيا في القدرة على العد التنازلي، حيت تم التوصل الى وجود فروق ذات دلالة احصائية في القياس البعدي بين المجموعة الضابطة والمجموعة التجريبية. وبالتالي تم التأكد على ضرورة الكشف المبكر للتلاميذ عسيري الحساب في المدارس الابتدائية ورياض الاطفال، لكي يتم التكفل بهم وتقديم خدمات تدريبية لتنمية قدراتهم الحسابية في مختلف المهارات وفي جميع المستويات الخاصة بالرياضيات، وذلك لتفادي الاثار السلبية لعسر الحساب على التحصيل الدراسي لاحقا. Study summary The study aimed to build a training program to develop the arithmetic ability of the fourth and fifth year students of primary school who suffer from difficulty in mathematics، and to identify the difference in the dimensional measurement between the control and experimental group. The study was conducted on a sample of (20) male and female students in some of the valley’s primary schools، and they were chosen in an intentional way، using a test that measures reading abilities at various levels، and it was represented in the following: Mental arithmetic ability test (adding، subtracting، multiplying and dividing numbers orally)، And the ability test to count down، and by following the experimental method with an experimental design with two control and experimental groups، and two measurements before and after، and to test the hypotheses of the study، the arithmetic mean and standard deviation were used، and the “t” test was applied to indicate the differences between the averages of two related samples، then the effect size was calculated، and the effect was reached. to the following results: The training program has achieved a positive effect in developing the arithmetic ability of the hard-to-arithmetic students at the level of mental arithmetic ability، as it was concluded that there are statistically significant differences in the dimensional measurement between the control and experimental group. A positive effect was achieved in the ability to count down، as it was found that there were statistically significant differences in the dimensional measurement between the control group and the experimental group. Consequently، it was emphasized the necessity of early detection of arithmetic students in primary schools and kindergartens، in order to take care of them and provide training services to develop their arithmetic abilities in various skills and at all levels of mathematics، in order to avoid the negative effects of dyscalculia on later academic achievement.
دراسة تجريبية لبعض الابتدائيات بولاية الوادي
مذكرة ماستر علم الاجتماع تخصص تربية خاصة
Keywords: صعوبات التعلم، صعوبة الحساب، صعوبة الرياضيات; Difficultés d'apprentissage, difficulté arithmétique, difficulté en mathématiques; Learning difficulties, arithmetic difficulty, math difficulty